Behavioral and molecular processing of visceral pain in the brain of mice: impact of colitis and psychological stress - Jain, Piyush; Hassan, Ahmed M.; Koyani, Chintan N.; Mayerhofer, Raphaela; Reichmann, Florian; Farzi, Aitak; schuligoi, Rufina; Malle, Ernst; Holzer, Peter (Frontiers in Behavioral Neuroscience, 2015)
Gastrointestinal disorders with abdominal pain are associated with central sensitization and psychopathologies that are often exacerbated by stress. Here we investigated the impact of colitis induced by dextran sulfate sodium (DSS) and repeated water avoidance stress (WAS) on spontaneous and nociception-related behavior and molecular signaling in the mouse brain. DSS increased the mechanical pain sensitivity of the abdominal skin while both WAS and DSS enhanced the mechanical and thermal pain sensitivity of the plantar skin. These manifestations of central sensitization were associated with augmented c-Fos expression in spinal cord, thalamus, hypothalamus, amygdala and prefrontal cortex. While WAS stimulated phosphorylation of mitogen-activated protein kinase (MAPK) p42/44, DSS activated another signaling pathway, both of which converged on c-Fos. The DSS- and WAS-induced hyperalgesia in the abdominal and plantar skin and c-Fos expression in the brain disappeared when the mice were subjected to WAS+DSS treatment. Intrarectal allyl isothiocyanate (AITC) evoked aversive behavior (freezing, reduction of locomotion and exploration) in association with p42/44 MAPK and c-Fos activation in spinal cord and brain. These effects were inhibited by morphine, which attests to their relationship with nociception. DSS and WAS exerted opposite effects on AITC-evoked p42/44 MAPK and c-Fos activation, which indicates that these transduction pathways subserve different aspects of visceral pain processing in the brain. In summary, behavioral perturbations caused by colitis and psychological stress are associated with distinct alterations in cerebral signaling. These findings provide novel perspectives on central sensitization and the sensory and emotional processing of visceral pain stimuli in the brain.